Detection of quantitative resistance loci associated with resistance to rice false smut (Ustilaginoidea virens) using introgression lines. (15th July 2013) - Zhou, Y.‐L.; Xie, X.‐W.; Zhang, F.; Wang, S.; Liu, X.‐Z.; Zhu, L.‐H.; Xu, J.‐L.; Gao, Y.‐M.; Li, Z.‐K.
<x xml:space="preserve">Abstract</x> False smut, caused by Ustilaginoidea virens, is a rice disease of increasing importance worldwide, with no source of high‐level resistance in the existing rice germplasm. To facilitate breeding varieties with good levels of field resistance to false smut, quantitative resistance loci (QRL) were identified using 213 introgression lines (ILs) from a cross between Teqing (recipient) and Lemont (donor) evaluated using natural infection at two hotspots of false smut in northeast China. Ten QRL affecting percentages of diseased hills, diseased panicles and diseased spikelets were detected and mapped to rice chromosomes 2, 3, 4, 6, 8, 10, 11 and 12. The Lemont alleles at all QRL increased false smut resistance. Four QRL (qFSR‐6‐7, qFSR‐10‐5, qFSR‐10‐2 and qFSR‐11‐2) had relatively larger and consistent effects across the two testing sites. Promising resistant ILs were identified, most of which had multiple QRL, suggesting that pyramiding multiple QRL by marker‐assisted selection would be an effective strategy for improving rice resistance to false smut. The identified QRL and their linked DNA markers will facilitate this breeding effort in the future.